Swedish - Finnish glossary: church service words - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with church service words. Contains approximately 300 entries. 2014.

Swedish - Finnish glossary with church service words. Contains approximately 300 words. 2014.

En svensk-sverigefinsk ordlista med gudstjänstord. Innehåller ca 300 uppslagsord. 2014.
Svensk-finsk ordlista: gudstjänstord
Keywords: religious ceremonies; religiösa ceremonier; christianity; kristendom; Ceremonial Behavior; Ceremoniellt beteende; Christianity; Kristendom; Religion; Religion; glossary; ordlista; religion; religion; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur